PERANCANGAN ALAT BANTU SCREEN SABLON YANG ERGONOMIS PADA AKTIVITAS WINDOW PATCING UNTUK MENGURANGI KELUHAN MOSCULETAL DISORDER DI PT. XYZ - Sukma Kus Adhiyana Adhi; Afif Fawa Idul Fata; Rikzan Bachrul Ulum (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2023)
Work aids are tools used to make it easier for workers to carry out their daily activities to lighten a job. At PT XYZ found several complaints of muscle pain in several parts of the worker's body in the window patching section. To reduce the complaints experienced by window patching operators, the method used is the Standard Nordic Questionnaire and Ergonomics. This method is used to identify the source of the cause of muscle fatigue at work while ergonomics is used to determine the dimensions of the assistive devices to be designed according to human anthropometry. Calculation of the overall percentage of each of the questionnaire questions, obtained an average of the largest complaints on the body of the right upper arm by 68.8%, right elbow by 87.5%, right forearm by 81.3%, and wrist right hand by 87.5%. The results of making a manual window patching tool using the 50th percentile with a table height tool size of 88 cm, a tool width of 38 cm, a tool length of 43 cm, a beam width of 18 cm, and a pushing distance of 71 cm.Keywords: Tool Design; Window patching; SNQ; Ergonomics; Anthropometry